DNA-based identification of forensically significant beetles from Southern Africa - Collett, Isabel Judith (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2015)
Necrophilous insects, if correctly identified, can provide useful forensic information. Research in this area has focussed on flies and beetles remain comparatively under-studied, partly because some adult carrion beetles are difficult to identify morphologically, as are their juvenile stages, often requiring specialist expertise in both cases. Molecular taxonomy has been proposed as a solution to these problems. DNA "barcodes" are short fragments of mitochondrial cytochrome oxidase I (COI) DNA that are anticipated to delineate species. This approach is becoming increasingly popular, but has been met with varying enthusiasm from taxonomists. This thesis examines their use in identifying forensically significant beetles.The DNA barcodes of 234 specimens of 25 forensically significant southern African beetle species from seven families (Cleridae, Dermestidae, Silphidae, Staphylinidae, Scarabaeidae, Trogidae and Histeridae) were obtained. Thirty-three initial barcode amplification failures were overcome by using primers other than the standard Folmer pair, undermining the barcode concept's hope of universal primers that would allow even non-specialists to produce barcodes. Another 150 specimens (64%) entirely failed to yield barcodes, including 18 fresh specimens of three species of Trogidae, implying another lack of universality of the barcoding protocol. The majority of the beetles clustered with confamilials on neighbour-joining and maximum likelihood trees, but 1.3% of the barcodes failed to cluster with their respective families, raising questions concerning the associating power of barcodes. The identification tools of the GenBank and BOLD on-line DNA sequence databases identified 21% of the specimens to the species level, 6% of them correctly. There was evidence of a paralogous sequence in the Cleridae that, while supporting identification now that it has been associated with a morphological identification, would hamper attempts at identification by clustering or phylogenetic analysis.Distance and haplotype network analyses of the barcodes of six widespread species showed that they are not geographically structured. Barcodes are thus unlikely to be indicators of the region of origin of a species and will not determine whether a corpse has been relocated after death. To assess whether a different mitochondrial DNA fragment might address (some of) these problems, a 2.2 kb fragment extending from the 5' end of the COI gene to the 3' end of the Cytochrome Oxidase II (COII) gene was analysed for nine species. It was found that, for Dermestidae, Scarabaeidae and Histeridae, higher degrees of diversity occurred downstreamof the barcode region, but the region of highest diversity in the Cleridae was in the barcode region. Thus, finding a more reliable fragment along the COI-COII region for each family may make robust and guaranteed DNA-based identification of these beetles more likely. The possibility of a forensic specimen being incorrectly or not identified based on its barcode alone exists in about 40% of cases, even with the new barcodes reported here. Forensic science sets a very high bar in assessing the performance of its techniques, and it is concluded that barcodes currently have unsettling failure rates as court-worthy evidence.
Keywords: Carrion insects; Forensic entomology; Cleridae; Dermestidae; Silphidae; Staphylinidae; Scarabaeidae; Histeridae